Vowel lengthening as a sociolinguistic feature of Vilnius speech - Čičirkaitė, Ramunė; Vaicekauskienė, Loreta (Taikomoji kalbotyra, 2012)
The paper focuses on vowel lengthening in Vilnius speech. This feature has been stigmatised by Lithuanian language planners as a feature of Slavic origin, which has influenced Vilnius speech and therefore has to be avoided as non-standard and incorrect. The aim of the study was to find out how frequent the lengthening of short vowels is in the speech of Vilnius and how it depends on linguistic and social factors and self-monitoring of speech. The research is based on the classical Labovian interview with seventeen second and third generation residents of Vilnius (aged 18–40), 4.5 hours of speech in total. The research has shown that vowel lengthening is far from common in Vilnius speech. It depends largely on the type of syllable and the place of stress; the lengthening mostly affects just stressed syllables and usually in word stem. The lengthening of short inflectional endings, which is highly associated with Russian or Polish accent and regarded as the worst feature of urban speech, seems to be extremely rare. It has also been shown that the tendency to lengthen manifests itself quite consistently; informants who lengthen stressed vowels in the stem of the word more often than others tend to lengthen syllables at the end of the word. This applies to all contextual styles. In spite of relatively big individual difference in speech of informants, the research revealed that vowel lengthening in Vilnius speech is mostly used by the oldest of our informants and by men more than women. The dependence of vowel lengthening on contextual style turned out to be quite controversial and may point to the development of different speech norms in Vilnius.